The animacy advantage in memory occurs under self-paced study conditions, but participants’ metacognitive beliefs can deter it - Serra, Michael J.; DeYoung, Carlee M. (Frontiers in Psychology, 2023)
Introduction Animacy distinguishes living (animate) things from non-living (inanimate) things. People tend to devote attention and processing to living over nonliving things, resulting in a privileged status for animate concepts in human cognition. For example, people tend to remember more animate than inanimate items, a phenomenon known as the “animacy effect” or “animacy advantage.” To date, however, the exact cause(s) of this effect is unknown. Methods We examined the animacy advantage in free-recall performance under computer-paced versus self-paced study conditions and using three different sets of animate and inanimate stimuli (Experiments 1 and 2). We also measured participants’ metacognitive beliefs (expectations) about the task before it began (Experiment 2). Results We consistently obtained an animacy advantage in free-recall, regardless of whether participants studied the materials under computer-paced or self-paced conditions. Those in self-paced conditions spent less time studying items than did those in computer-paced conditions, but overall levels of recall and the occurrence of the animacy advantage were equivalent by study method. Importantly, participants devoted equivalent study time to animate and inanimate items in self-paced conditions, so the animacy advantage in those conditions cannot be attributed to study time differences. In Experiment 2, participants who believed that inanimate items were more memorable instead showed equivalent recall and study time for animate and inanimate items, suggesting that they engaged in equivalent processing of animate and inanimate items. All three sets of materials reliably produced an animacy advantage, but the effect was consistently larger for one set than the other two, indicating some contribution of item-level properties to the effect. Discussion Overall, the results suggest that participants do not purposely allocate greater processing to animate over inanimate items, even when study is self-paced. Rather, animate items seem to naturally trigger greater richness of encoding than do inanimate items and are then better remembered, although under some conditions participants might engage in deeper processing of inanimate items which can reduce or eliminate the animacy advantage. We suggest that researchers might conceptualize mechanisms for the effect as either centering on intrinsic, item-level properties of the items or centering on extrinsic, processing-based differences between animate and inanimate items.